KAJIAN STATUS MUTU PERAIRAN SUNGAI SERAYU DENGAN MENGGUNAKAN PENDEKATAN METODE INDEKS PENCEMARAN (POLLUTION INDEX) - Nurlinda Ayu Triwuri; Murni Handayani; Rosita Dwityaningsih (Yayasan Akrab Pekanbaru, 2018)
Serayu River crossing several districts Wonosobo, Banjarnegara, Purbalingga, Banyumas, until empties into Cilacap. This research was conducted at Banyumas and Cilacap regency. Banyumas Regency, Kebasen consists of three stations in the sand mining area before sand mining, sand mining location, after sand mining. Cilacap regency consists of three stations Sampang, Maos and Slarang. The method used there are two that is purposive sampling method for sampling location and method of pollution index (IP) to determine water quality of Serayu River. From the calculation of IP method, the water quality of Serayu River in Banyumas Regency is obtained at station 1, 2 and 3 (0,922), (0,921) and (0,934). Meanwhile, located in Cilacap Regency, obtained at stations 1, 2 and 3 of (0.897), (0.921) and (0.891). Based on Ministry Decree No.115/2003 relationship value of IP with water quality status is still included in the IP value of 0 to 1.0 is the status of good condition quality. Keyword : Serayu River, Pollution Index, Quality status.